Methods for designing Internet telephony services with fewer feature interactions - Chan, Ken Yat-Wan (University of Ottawa (Canada), 2003)
This thesis describes a practical formal approach to designing Internet (IP) Telephony services with fewer feature interactions using SDL and Message Sequence Charts (MSC). Feature interactions are undesirable side effects caused by interactions between features and/or their environment. These undesirable side effects are known to affect the construction of reliable software systems. The IETF 'Session Initiation Protocol' (SIP) is chosen as the IP telephony signaling protocol for the case study of this thesis. Although IP Telephony services do not have some of the traditional feature interactions, the service designers are confronted with new feature interaction problems. We have proposed an extension to the classical feature interaction classification system. The main contribution of this thesis is our formal SDL model of SIP and its sample services that are derived from informal SIP specification. We apply use case analysis to some informal extent in our design, and specify SIP services more precisely by creating an "Abstract User interface". (Abstract shortened by UMI.)
Keywords: Engineering, Civil.; Engineering, Electronics and Electrical.